Bright lights, big christmas eaudiobook A novel. - Andrews, Mary Kay (Macmillan Audio, 2023)
Narrator Kathleen McInerney will have listeners believing in miracles." — AudioFile on The Santa Suit From Mary Kay Andrews, New York Times bestselling author of The Homewreckers and The Santa Suit , comes a novella celebrating love and the warm, glittering charm of the holiday season. "Nobody does Christmas like Mary Kay Andrews." ―Debbie Macomber "Cozy up with Santa's favorite novelist!" ―Adriana Trigiani When fall rolls around, it's time for Kerry Tolliver to leave her family's Christmas tree farm in the mountains of North Carolina for the wilds of New York City to help her gruff older brother & his dog, Queenie, sell the trees at the family stand on a corner in Greenwich Village. Sharing a tiny vintage camper and experiencing Manhattan for the first time, Kerry's ready to try to carve out a new corner for herself. In the weeks leading into Christmas, Kerry quickly becomes close with the charming neighbors who live near their stand. When an elderly neighbor goes missing, Kerry will need to combine her country know-how with her newly acquired New York knowledge to protect the new friends she's come to think of as family, And complicating everything is Patrick, a single dad raising his adorable, dragon-loving son Austin on this quirky block. Kerry and Patrick's chemistry is undeniable, but what chance does this holiday romance really have? Filled with family ties, both rekindled and new, and sparkling with Christmas magic, BRIGHT LIGHTS, BIG CHRISTMAS delivers everything Mary Kay Andrews fans adore, all tied up in a hilarious, romantic gem of a novel. A Macmillan Audio production from St. Martin's Press.